Consumer Awareness of Green Marketing and Buying Behavior: A Synthesis of Literature - Rawal, Dhavindra; Aryal, Bhoj Raj (Contemporary Research: An Interdisciplinary Academic Journal, 2024)
The purpose of this study is to present the systematic review of the literature on green marketing. Green marketing is a burning issue in the global environmental protection context and it is necessary mater to discuss our consumption behavior, business patterns, and national policy to support environmentalism. As consumer and society become more concerned about natural environment, modify their buying behavior in an attempt to address their well-being. This study has synthesized the specified literature related to consumer awareness and their buying behavior in environmental marketing. The review of literature is based on limited theoretical and empirical studies. Based on the literature, the study concluded that there is a significant relationship between the green awareness of consumers and their buying behavior. In addition, green information and promotion activities help to increase the level of green awareness that leads to a change the green buying behaviour in marketing practices. Green consumers play a vital role in the protection of the environment.